Social movements and ethnic media: Between critical and decolonial dialogues in digital networks (Research, Society and Development, 2024)
Communication and communication practices in contemporary times use language as an instrument of power and social domination. In this sense, the general objective of this study is to analyze social movements and ethnic media, among critical and decolonial dialogues on digital networks. Methodology: This is a qualitative narrative bibliographic research. It was concluded that throughout the study, the analyses, problematizations and representations carried out by ethnic social movements are not exhausted here, nor are the perspectives of critical, decolonial studies assumed in this research as a distinctive feature among the movements. The media is a work that, in an approximate and reflexive way, seeks to problematize the (re)affirmative constructions regarding the process of identification of the indigenous being in this surrounding society. Thus, what has been exposed on social networks is part of its meaning. What is broadcast/publicized is part of the struggles for rights and the ‘mobilization networks’.